Ptolemaic Alexandria according to the perspective of Global History - Climaco, Joana Campos (Romanitas - Revista de Estudos Grecolatinos, 2023)
Alexandria was founded on the Egyptian Mediterranean coast by King Alexander III of Macedon at the start of his campaign against the Achaemenid-Persian Empire (332/331 BCE). In the following decades, the seaside city replaced Memphis as the seat of monarchical power in Egypt. Its development reconfigured the urban and political dynamics in the former Nilotic territory and formalized the Greek presence in the Delta, at that time through its insertion also in the Egyptian command. In dialogue with the recent perspectives of Global History, the expectation of this article is to rethink the history of Alexandria by discussing how the foundation and initial history of the city made it a place conducive to mobility and interlinking.